Social and Economic Factors in the Formation of Political Intelligence in Hamparan Perak Village, Deli Serdang Regency - Gultom, Wida Bonor; Hasibuan, Ramadani Sohiro; Sabrina, Salwa; Br Tambunan, Yusna Elfrida; Halking, Halking (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study analyzes the political intelligence of rural communities, which is influenced by local education, social, economic, and cultural structures. A good education improves political understanding, while limited education and access to information are often obstacles. Indigenous and religious leaders play a major role in shaping political opinions, while economic conditions and dependence on government assistance also influence political preferences. Social media is starting to play a role in expanding access to information, even though it is vulnerable to hoaxes. Through qualitative methods, this study finds that people's political participation is influenced by economic motivation and social structure. In conclusion, political education is needed from parties and community leaders to increase citizens' awareness and political responsibility.